Повторение пройденного: повесть / Тамара Крюкова - Крюкова Тамара Шамильевна (Смешные истории, 2008)
Экземпляры: ф.4 (20160713) / Инвентарный номер: 2612 / Цена: / Сис.шифр: 84(2Рос=Рус)6-7 / Авт.знак: К 85 / ГРНТИ: 17.82.93 / ББК: 84(2Рос=Рус)6-7